Endoscopic stenting in colorectal cancer - Lim, Tian-Zhi (J Gastrointest Oncol, 2019)
Acute malignant large bowel obstruction presents as one of the few emergencies of colorectal cancer (CRC). Management of this condition can either be by (I) upfront surgery or (II) the use of self-expanding metallic stent (SEMS) as a bridge to elective surgery. For patients with metastasis, the use of SEMS is reported to enable earlier commencement of chemotherapy. Although the use of SEMS in patients with acute malignant large bowel obstruction looks promising, it is plagued by its own set of complications and divided opinion over its long-term outcomes. Conflicting data are present, and definitive indication requires further evaluation and debate. This article will describe the typical presentation of patients with acute malignant large bowel obstruction. An introduction to the SEMS insertion procedural steps will be undertaken. Following which the article aims to review the safety profile of SEMS and the short- and long-term outcomes of SEMS in both the curative and palliative setting.